Multifunctional nanomaterials for cancer theranostics applications - Anderson, Tommy (2017)
Limited success in early diagnosis of pancreatic cancer, combined with lack of effective treatment options have resulted in low survival rate for pancreatic cancer patients. Current therapy option such as chemotherapy poses toxic side effects and low therapeutic efficacy. In our work, we aim to solve this challenge by utilizing multifunctional nanomaterials for cancer theranostics applications. Organic biodegradable nanomaterials such as cationic polylactides were applied for RNA interference gene therapy for pancreatic cancer and their efficiency and therapeutic efficacy were evaluated. We investigated applications of inorganic materials with interesting properties, such as 1-dimensional carbon nanotubes, 0-dimensional graphene quantum dots, and 2-dimensional transition metal dichalcogenides. Functionalization of these nanomaterials was carried out to improve their biocompatibility and allow conjugation with therapeutic materials to act as efficient transfection agent for gene therapy in pancreatic cancer cells. Intrinsic properties of these nanomaterials are also advantageous for application such as imaging of cancer cells. In these works, we investigated and demonstrated the application of nanomaterials and their potential for improvements in cancer theranostics, especially in gene therapy and imaging of pancreatic cancer.